Health Effects of a Religious Vocation: Perspectives from Christian and Jewish Clergy. (December 2016) - Webb, Benjamin; Bopp, Melissa; Baruth, Meghan; Peterson, Jane
Clergy often serve in multiple capacities within religious organizations, making them indispensable to the day-to-day operations of these organizations. Although quantitative studies have highlighted negative health outcomes among clergy, whether this can be attributed to characteristics of the clergy vocation is poorly understood. To explore this possibility, this article presents perspectives from Christian and Jewish clergy about how the religious vocation has affected their health.